Watson-Crick linear grammars - Mohamad Zulkufli, Nurul Liyana; Turaev, Sherzod; Mohd Tamrin, Mohd Izzuddin; Messikh, Azeddin (2015)
In this paper, we define Watson-Crick linear grammars ex- tending Watson-Crick regular grammars [9] with linear rules, and study their generative power. We show that Watson-Crick linear grammars can generate some context-sensitive languages. Moreover, we establish that the family of Watson-Crick regular languages proper subset of the family of Watson-Crick linear languages but it is not comparable with the family of linear languages.